Exploring Attachment and Internal Representations in Looked-After Children - Hillman, Saul; Cross, Richard; Anderson, Katharine (Frontiers in Psychology, 2020)
Background This article explores the Story Stem Assessment Profile (SSAP), a narrative-based measure, for the assessment of internal representations in children between the ages of 4 and 11 years old. Methods The findings draw upon two samples of children comprising of a sample of looked-after children at Five Rivers Child Care (FR) (n = 42) and a community-based population (n = 42). The FR group identified were suggested to have a higher level of need, as defined by scores obtained from the Strengths and Difficulties Questionnaire (SDQ) and Relationship Problems Questionnaire (RPQ). Results Using the SSAP, the findings indicate the instrument’s discriminant validity with strong differences being displayed between the two populations. Consistently children in the FR sample displayed more disorganized, avoidant and negative representations, whilst at the same time having significantly fewer representations characteristic of ‘secure’ attachment. Conclusion The SSAP is successful in differentiating between ‘low’ and ‘high’ cohorts of children aged 4–11 years. The study provides strong support for the measure as a way of capturing internal and attachment representations, with further research to explore possible changes in these representations at follow-up being promising and intriguing. Continued research efforts at FR will allow for improved clinical formulations, increased understanding and therefore positive outcomes relating to the children in their care.